Harnessing Functional Foods and Medicinal Plants for Managing Sickle Cell Anaemia in Nigeria: A Review - Mohammed Danyaro, Abdulkadir; Aminu Bello, Bello; Suleiman Mohammed, Zinat; Sadiq Tanko, Abubakar; Mallam Ado, Ahmad; Abdullahi Adam, Adam; Aliyu Nuru, Khadija (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Haemoglobinopathies are inherited erythrocytes’ dysfunctions, caused by autosomal genetic changes like a single nucleotide change in a gene or the decreased production of at least one globin chain that result in unbalanced haemoglobin synthesis, anaemia and other complications. The diseases can be managed through blood transfusion or use of approved conventional therapeutics like hydroxyurea, voxelotor, crizanlizumab, L-glutamine, L-arginine and nutritional supplements. However, these are either unaffordable to majority of people with the disease or pose some side effects, which compel patients to resort to use of functional foods and medicinal plants for treatment. These functional foods and medicinal plants in Nigeria are being used to inhibit or reverse sickling of red blood cells by exploiting the allosteric nature of haemoglobin S to inhibit it from assuming a tensed state or reverse it from such state. They are also employed to exert significant pain relief in patients. Therefore, this work exploited peer-reviewed articles form PubMed and Google Scholar to harness the functional foods and medicinal plants locally employed by Nigerians in the treatment of the most prevalent erythrocytes’ dysfunctions (sickle cell anaemia), indicating their interactions with the structure of haemoglobin and some cellular receptors as well as the potentials of exploiting them for the development of drugs or nutraceuticals with antisickling and anti-nociceptive effects. However, despite their promising potentials in sickling management, challenges like bioavailability, inadequate molecular understanding of antisickling pathways and limited clinical evidence remain. Addressing these issues through standardizing phytochemical profiles, deepening the molecular understanding of antisickling pathways and clinical trials is crucial for their effective therapeutic application.